Qur'anic Covenants Reconsidered mīthāq and ʿahd in Polemical Context - O'Connor, Andrew J. (2019)
This article examines the Qur'an's use of 'covenant' (Arabic ʿahd and mīthāq). Recent scholarly attention to covenants in the Qur'an has hitherto largely hinged on modern questions of inclusivism, pluralism, or notions of Islamic salvation history. Most studies have focused on Q 7.172 (and its interpretations), which is usually treated as the most important covenantal verse in the Qur'an. The analysis here is intended to be not an exhaustive study of covenant in the Qur'an, but an attempt to re-orient the discussion in terms of the qur'anic usage as distinct from later categories, and to move away from the tendency to prioritize Q 7.172 as the central covenant verse. The article pays particular attention to the way in which the Qur'an re-contextualizes 'covenant' for its own theological ends, and argues that the Qur'an uses this motif for a multiplicity of purposes. To this end it highlights three elements of the Qur'an's covenant theology: (1) its prophetological connotations, (2) its association with legal injunctions and the Decalogue, and (3) its eschatological implications. All three components often serve polemical functions. The article also makes some brief observations concerning the relationship between the Qur'an's use of covenant and its Late Antique context.
Keywords: Late Antiquity; Qur'an; Covenant; Eschatology; Prophetology